1st Annual Applied Science and Engineering Conference (AASEC), in conjuction with The International Conference on Sport Science, Health, and Physical Education (ICSSHPE). (March 2017) - Unknown
Abstract : PREFACE The 1st Annual Applied Science and Engineering Conference (AASEC 2016) in conjunction with The International Conference on Sport Science, Health, and Physical Education (ICSSHPE) is motivated by improving the quality of research and development relating to the applied science and engineering. AASEC brings a theme of "Empowering Young Researchers in the Field of Science and Engineering". Thus, this conference has aims: (1) to bring together the scientists, engineers, researchers and practitioners, students, and civil society organization representatives in the scientific forum. (2) To share and to discuss theoretical and practical knowledge about innovation in applied science and engineering. The conference is hosted by the UPI Publication Center, Universitas Pendidikan Indonesia. Specifically, this conference can be used as a scientific forum for accommodating discussion among young researchers that originated from Indonesia in the field of applied science and engineering. Therefore, the invited speakers in this conference are young researchers that are well-known and reputable in the world. The conference took place in Bandung, Indonesia, on 18 November 2016. More than 500 papers are participated from various topics including engineering and technology innovation, engineering education, vocational education and training, and innovation in teaching and learning. There are 298 selected papers that go through a strict peer reviewed process, and these papers will be published in the present conference proceedings. We would like to thank the organizing committee and the members of reviewers for their kind assistance in reviewing the papers. We would also extend our best gratitude to keynote speakers for their invaluable contribution and worthwhile ideas shared in the conference. The Editors Dr. Ade Gafar Abdullah Dr. Eng. Asep Bayu Dani Nandiyanto Ari Arifin Danuwijaya, M.A.